(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article analyzes the methodology of problem-based teaching of ultrasound diagnostics aimed at forming clinical thinking in medical education. The research presents a pedagogical approach that develops differential diagnostic skills. Educational sessions structured on problem situations enhance students’ independent analytical abilities. The methodology was practically tested in teaching medical radiology and yielded positive results demonstrating improved reasoning capacity among learners.